What my mother doesn't know - Sones, Sonya (New York : Simon Pulse, 2003)
Sophie describes her relationships with a series of boys as she searches for Mr. Right.
5.8
Young Adult
Young Adult
Wilson's Junior High School
Notable/Best Books (A.L.A.)
School Library Journal
Keywords: Dating (Social customs) -- Fiction; Love -- Fiction; Dating (Social customs) -- Fiction; Love stories